ANALISIS KAPASITAS FISKAL DAN PENGARUHNYA TERHADAP ANGGARAN BELANJA MODAL ( STUDI EMPIRIS PADA PEMERINTAH KABUPATEN/KOTA DI PULAU SUMATERA PERIODE 2009 – 2013 ) - Liza Fiona; Taufeni Taufik; Vince Ratnawati (Fakultas Ekonomi dan Bisnis, Universitas Riau, 2016)
This study aims to determine the effect of Local Own Revenue, Revenue Sharing,General Allocation Funds, Other Local Revenues, and Personnel Expenditureaffect the Capital Expenditure Budget District / City Government on the island ofSumatera.The population in this study is the district / city governments in Sumatra 2009-2013. By using purposive sampling method, of 151 regencies / cities in Sumatraobtained a sample of 122 district / city. This research is a quantitative researchusing secondary data. Testing the hypothesis in this study using multiple linearregression with t test, and the coefficient of determination. The results showedthat the Local Own Revenue, Revenue Sharing, General Allocation Fundssignificant affect Budget Capital Expenditure, Other Local Revenue no effect onthe Budget Capital Expenditure, while personnel expenditure have a significanteffect but with a negative direction.